Aesthetic Pleasure and Negative Aesthetic Experience in the Old English Martyrology - Minaya Gómez, Francisco Javier (Studia Anglica Posnaniensia, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*120.50px); top: calc(var(–scale-factor)*349.86px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.926609);" role="presentation">Drawing on recent research on aesthetic emotions and folk aesthetics, the purpose of this paper is <span dir="ltr" style="left: calc(var(–scale-factor)*120.50px); top: calc(var(–scale-factor)*360.66px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.983478);" role="presentation">to look into <span dir="ltr" style="left: calc(var(–scale-factor)*163.22px); top: calc(var(–scale-factor)*360.66px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.9255);" role="presentation">the way <span dir="ltr" style="left: calc(var(–scale-factor)*192.77px); top: calc(var(–scale-factor)*360.66px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.893527);" role="presentation">aesthetic pleasure and negative aesthetic experience are described and rendered <span dir="ltr" style="left: calc(var(–scale-factor)*120.50px); top: calc(var(–scale-factor)*371.46px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.966857);" role="presentation">in the <span dir="ltr" style="left: calc(var(–scale-factor)*142.94px); top: calc(var(–scale-factor)*371.46px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.989412);" role="presentation">Old English Martyrology <span dir="ltr" style="left: calc(var(–scale-factor)*235.97px); top: calc(var(–scale-factor)*371.46px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0043);" role="presentation">(OEM). <span dir="ltr" style="left: calc(var(–scale-factor)*266.33px); top: calc(var(–scale-factor)*371.46px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.96241);" role="presentation">Using different Old English lexical tools and an edition of <span dir="ltr" style="left: calc(var(–scale-factor)*120.50px); top: calc(var(–scale-factor)*382.26px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.05447);" role="presentation">the OEM <span dir="ltr" style="left: calc(var(–scale-factor)*161.54px); top: calc(var(–scale-factor)*382.26px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.03693);" role="presentation">with a translation<span dir="ltr" style="left: calc(var(–scale-factor)*229.49px); top: calc(var(–scale-factor)*382.26px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.982834);" role="presentation">, this paper analyses these two aesthetic responses <span dir="ltr" style="left: calc(var(–scale-factor)*433.39px); top: calc(var(–scale-factor)*382.26px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.06246);" role="presentation">taking into <span dir="ltr" style="left: calc(var(–scale-factor)*120.50px); top: calc(var(–scale-factor)*393.06px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.926292);" role="presentation">consideration the context of <span dir="ltr" style="left: calc(var(–scale-factor)*221.21px); top: calc(var(–scale-factor)*393.06px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.9225);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*234.05px); top: calc(var(–scale-factor)*393.06px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.946579);" role="presentation">composition of <span dir="ltr" style="left: calc(var(–scale-factor)*289.73px); top: calc(var(–scale-factor)*393.06px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.9225);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*302.57px); top: calc(var(–scale-factor)*393.06px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.919471);" role="presentation">text and the possibility that it was aimed towards <span dir="ltr" style="left: calc(var(–scale-factor)*120.50px); top: calc(var(–scale-factor)*403.88px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.983225);" role="presentation">the emotional education of a particular religious community. <span dir="ltr" style="left: calc(var(–scale-factor)*350.11px); top: calc(var(–scale-factor)*403.88px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.31);" role="presentation">It <span dir="ltr" style="left: calc(var(–scale-factor)*358.99px); top: calc(var(–scale-factor)*403.88px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.96465);" role="presentation">argues that, to a certain extent, <span dir="ltr" style="left: calc(var(–scale-factor)*120.50px); top: calc(var(–scale-factor)*414.68px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.936968);" role="presentation">the author of the OEM standardises the aes<span dir="ltr" style="left: calc(var(–scale-factor)*279.17px); top: calc(var(–scale-factor)*414.68px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.947878);" role="presentation">thetic experiences that they narrate, both positive and <span dir="ltr" style="left: calc(var(–scale-factor)*120.50px); top: calc(var(–scale-factor)*425.48px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.946734);" role="presentation">negative, and associates them with particular religious and doctrinal messages that are aimed at <span dir="ltr" style="left: calc(var(–scale-factor)*120.50px); top: calc(var(–scale-factor)*436.28px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.929291);" role="presentation">providing sensory inputs through which the conceptualisation of abstract and religious experiences <span dir="ltr" style="left: calc(var(–scale-factor)*120.50px); top: calc(var(–scale-factor)*447.08px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.986842);" role="presentation">is f<span dir="ltr" style="left: calc(var(–scale-factor)*131.66px); top: calc(var(–scale-factor)*447.08px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.962459);" role="presentation">acilitated.